Gestational diabetes as a risk factor for GBS maternal rectovaginal colonization: a systematic review and meta-analysis - Vicki Mercado-Evans; Jacob J. Zulk; Zainab A. Hameed; Kathryn A. Patras (BMC, 2024)
Abstract Background Maternal rectovaginal colonization by group B Streptococcus (GBS) increases the risk of perinatal GBS disease that can lead to death or long-term neurological impairment. Factors that increase the risk of rectovaginal GBS carriage are incompletely understood resulting in missed opportunities for detecting GBS in risk-based clinical approaches. There is a lacking consensus on whether gestational diabetes mellitus (GDM) is a risk factor for rectovaginal GBS. This systematic review and meta-analysis aims to address current conflicting findings and determine whether GDM should be clinically considered as a risk factor for maternal GBS colonization. Methods Peer-reviewed studies that provided GDM prevalence and documented GBS vaginal and/or rectal colonization in women with and without GDM were included in this analysis. From study inception to October 30, 2023, we identified 6,275 relevant studies from EMBASE and PUBMED of which 19 were eligible for inclusion. Eligible studies were analyzed and thoroughly assessed for risk of bias with a modified Newcastle-Ottawa Scale that interrogated representativeness and comparability of cohorts, quality of reporting for GDM and GBS status, and potential bias from other metabolic diseases. Results were synthesized using STATA 18 and analyzed using random-effects meta-analyses. Results Studies encompassed 266,706 women from 10 different countries, with study periods spanning from 1981 to 2020. Meta-analysis revealed that gestational diabetes is associated with a 16% increased risk of rectovaginal GBS carriage (OR 1.16, CI 1.07-1.26, P = 0.003). We also performed subgroup analyses to assess independent effects of pregestational vs. gestational diabetes on risk of maternal GBS carriage. Pregestational diabetes (Type 1 or Type 2 diabetes mellitus) was also associated with an increased risk of 76% (pooled OR 1.76, CI 1.27-2.45, P = 0.0008). Conclusions This study achieved a consensus among previously discrepant observations and demonstrated that gestational diabetes and pregestational diabetes are significant risk factors for maternal rectovaginal carriage of GBS. Recognition of GDM as a risk factor during clinical decisions about GBS screening and intrapartum antibiotic prophylaxis may decrease the global burden of GBS on maternal-perinatal health.